Study of natural weathering exposure on properties of ldpe incorporated with sago starch - Kormin, Shaharuddin; Kormin, Faridah; Hossen Beg, Mohammad Dalour (2018)
In this study it was investigated the incorporation of sago starch in low-density polyethylene matrix (LDPE) to enhanced mechanical properties and to obtain partially biodegradable product with the aim to reduce the plastics wastes in the environment. The compounding of the LDPE with sago starch was prepared via a twin screw extruder followed by injection molding. Studies on their physical, mechanical properties and thermal properties of each formulation before and after natural weathering exposure were carried out by tensile, thermogravimetry analyzer (TGA-DTA) and scanning electron microscope (SEM). The biodegradability of sago starch–filled LDPE blend was studied by monitoring its weight loss. Tensile tests, TGA and SEM imaging were also carried out on the samples before and after degradation. Imaging showed that the increase in starch content from 5% to 20% in the formulations increases the biodegradability of the samples.